A importância do Instituto Nacional de Pesquisa do Pantanal para o conhecimento e a preservação do bioma Pantanal e o entendimento de suas interações ecológicas - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2017)
Created to integrate the networks and research groups and to train human resources in the different areas of knowledge in and under the Pantanal biome, the National Institute of Pantanal Research (INPP) (currently established as a Campus of the Museu Paraense Emílio Goeldi - MPEG, in Cuiabá, Mato Grosso) shows in this special edition of the Bulletin of the Museu Paraense Emílio Goeldi. Natural Sciences, its action in the sense of aggregate, foment and form groups of different institutions of Brazil, that are acting and publishing together. The authors' different specialties and subjects on the Pantanal included in this publication indicate that the action coordinated by MPEG is having encouraging results.
The importance of the Pantanal's National Research Institute for knowledge and preservation of the Pantanal biome and the understanding of its ecological interactions
Keywords: Pantanal; preservação; bioma; interações ecológicas; CNPQ::CIENCIAS EXATAS E DA TERRA